Chest pain centers: a comparison of accreditation programs in Germany and the United States - Breuckmann, Frank; Burt, David R.; Melching, Kay; Erbel, Raimund; Heusch, Gerd; Senges, Jochen; Garvey, J. Lee (Critical pathways in cardiology, 2015)
Objective: - The implementation of chest pain centers (CPC)/units (CPU) has been shown to improve emergency care in patients with suspected cardiac ischemia. - Methods: - In an effort to provide a systematic and specific standard of care for patients with acute chest pain, the Society of Cardiovascular Patient Care (SCPC) as well as the German Cardiac Society (GCS) introduced criteria for the accreditation of specialized units. - Results: - To date, 825 CPCs in the United States and 194 CPUs in Germany have been successfully certified by the SCPC or GCS, respectively. Even though there are differences in the accreditation processes, the goals are quite similar, focusing on enhanced operational efficiencies in the care of the acute coronary syndrome patients, reduced time delays, improved diagnostic and therapeutic strategies using adapted standard operating procedures, and increased medical as well as community awareness by the implementation of nationwide standardized concepts. In addition to national efforts, both societies have launched international initiatives, accrediting CPCs/CPU in the Middle East and China (SCPC) and Switzerland (GCS). - Conclusion: - Enhanced collaboration among international bodies interested in promoting high quality care might extend the opportunity for accreditation of facilities that treat cardiovascular patients, with national programs designed to meet local needs and local healthcare system requirements.
Gesehen am 28.05.2020